Plato and Iris Murdoch: Good, Love, and the Recovering of Ancient Virtue Ethics in British Moral Philosophy (Revista Archai, 2019)
Since G. E. M. Anscombe’s famous article Moral Modern Philosophy was published in 1958, a consensus has been established around the moral philosophy’s need for expanding its analysis agenda beyond the notion of duty and obligation. This movement has resulted in the recovery of ancient moral conceptions focused on the constitution of a virtuous character and happiness, especially under the influence of Aristotle and Stoic philosophers. In this paper, I intend to show that the British novelist and philosopher Iris Murdoch engaged in this movement assuming some central notions of Plato’s moral philosophy as part of her criticism against the British moral philosophy of her age. Such criticism contends the replacement of the modern notion of a rational will by other platonic ideas, especially “love” and “Good”, understood as parts of an objective model of moral guidance. Unlike Plato, however, the Good and its power of engagement and attraction were not characterized in a metaphysical way but as a peculiar psychological and moral notion. Following Freud’s psychoanalysis, the Good is conceived as part of XX lovely attention to the other and as a desire to see the reality behind our egoism and the pitfalls of imagination, which gives a psychological-naturalistic flavor to Murdoch’s claim from Plato’s philosophy.